In situ modified screen printed and carbon paste ion selective electrodes for potentiometric determination of naphazoline hydrochloride in its formulation - Gehad G. Mohamed; F.A. Nour El-Dien; Eman Y.Z. Frag; Marwa El-Badry Mohamed (Elsevier, 2013)
The construction and performance characteristics of new sensitive and selective in situ modified screen printed (ISPE) and carbon paste (ICPE) electrodes for determination of naphazoline hydrochloride (NPZ-HCl) have been developed. The electrodes under investigation show potentiometric response for NPZ-HCl in the concentration range from 7.0Ã10â7 to 1.0Ã10â2 M at 25Â Â°C and the electrode response is independent of pH in the range of 3.1â7.9. These sensors have slope values of 59.7Â±0.6 and 59.2Â±0.2Â mVÂ decadeâ1 with detection limit values of 5.6Ã10â7 and 5.9Ã10â7Â M NPZ-HCl using ISPE and ICPE, respectively. These electrodes show fast response time of 4â7Â s and 5â8Â s and exhibits lifetimes of 28 and 30 days for ISPE and ICPE, respectively. Selectivity for NPZ-HCl with respect to a number of interfering materials was also investigated. It was found that there is no interference from the investigated inorganic cations, anions, sugars and other pharmaceutical excipients. The proposed sensors were applied for the determination of NPZ-HCl in pharmaceutical formulation using the direct potentiometric method. It showed a mean average recovery of 100.2% and 102.6% for ISPE and ICPE, respectively. The obtained results using the proposed sensors were in good agreement with those obtained using the official method. The proposed sensors show significantly high selectivity, response time, accuracy, precision, limit of detection (LOD) and limit of quantification (LOQ) compared with other proposed methods. Keywords: ISPE and ICPE, Potentiometry, Naphazoline hydrochloride, Eye drops